CLINICAL MANIFESTATIONS OF THE DISEASE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Shermatova Zuhra Abduhamidovna (Bright Mind Publishing, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease characterized by multiple organ and system involvement. The clinical picture of SLE is polymorphic, which complicates timely diagnostics. The article discusses the most typical clinical manifestations of SLE with an emphasis on the systemic nature of the lesion and possible diagnostic difficulties. The immune system is a unique system of the human body that is able to distinguish "self" from "foreign", thereby providing protection against infections. Autoimmune diseases are a consequence of the activation of autoreactive T- and B-cells for reasons that are still unclear. Systemic lupus erythematosus (SLE) is a prototype of autoimmune diseases in which various systems and organs are affected. Most autoimmune diseases, including SLE, are considered as complex diseases, the manifestation of which involves environmental and genetic factors. Therapy for such diseases is not selective and extremely aggressive, which does not have the best effect on the quality of life of patients. The study of the genetic basis of autoimmune diseases is necessary to understand the pathogenetic mechanisms and discover new ways of therapy at a more advanced level - the genome level. Systemic lupus erythematosus (SLE) is a multisystem disease of unknown etiology, in which the immune system attacks its own cells and tissues. The disease is more common in women aged 15-45 years. Diagnosis is complicated by the variety of clinical manifestations and the possible involvement of almost any organ. SLE is inherited contrary to simple Mendelian laws and has a polygenic inheritance model. In some cases, SLE is associated with rare but highly specific mutations. For example, with homozygous deficiency of early components of the complement system Clq , C2 or C4. It is known that with a complete deficiency of the complement component C4, systemic lupus erythematosus develops in more than 75% of cases. However, studies devoted to the study of the genetic basis of deficiency of early complement components, including C4, are not numerous. This may be due to the labor-intensive nature of research into the unique region of the genome in which the C4 genes are located.